You Have My Word Confronting Critical Questions Involving Journalists’ Promises and Confidential Sources - Fernandez, Joseph (Sage Journals, 2015)
Journalists’ reliance on confidential sources for their articles is a lynchpin of journalistic practice. If journalists are unable to provide certain sources anonymity, ‘it is likely that critical information benefiting the public will not be passed on’ (Wade, 2014, p. 555). Public debate is thereby damaged as it ‘hides corruption, it undermines accountability and it fundamentally undermines the capacity for society to provide a safer, nurturing environment in which citizens can participate’ (ibid.). This article focuses on three important aspects of journalist source confidentiality: journalists’ authority to give confidentiality undertakings; the entry into such undertakings; and the types of sources, including the related question of who instigates such undertakings. This study draws on the results of an Australian survey conducted in 2014.